Manajemen Hubungan Pelanggan dan Pengaruhnya terhadap Loyalitas Konsumen: Wawasan dari Tinjauan Literatur yang Ekstensif - Siregar, Akhmad Irwansyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
Customer Relationship Management (CRM) is a crucial strategic approach for managing a company's interactions with customers to foster long-term loyalty. This study is a systematic literature review of recent studies from 2020 to 2024 that examine the relationship between CRM and customer loyalty. It maps the study's position within the existing literature. The results indicate that CRM contributes significantly to customer loyalty by increasing satisfaction and trust. However, there is variation in the influence of CRM components. The study also reveals that most studies focus more on the direct relationship between CRM and loyalty, exploring intervening factors and customer dynamics within the digital ecosystem.